HABITUS SISWA BERPRESTASI EKTRAKULIKULER TAPAK SUCI SMA MUHAMMADIYAH 10 SURABAYA - Sujianti, Neny (Paradigma, 2021)
Abstract Pencak silat is an intangible heritage recognized by Unesco. As a citizen, it is obligatory to preserve culture. The head of the pencak silat federation, Mr. Prabowo Subianto, has a way of trying to include pencak islat in the world of education. this received a positive response from Muhammadiyah, which has a sacred footprint. Muhammadiyah, which is also involved in the world of education, has many educational institutions that are spread throughout the country from elementary, middle, high school, to university. This is the field of introduction to the sacred site. as done by SMA Muhammadiyah 10 Surabaya or called SMAMX. SMAMX introduces itself as a gifted school that has more than forty-five active extracurriculars. Tapak Suci thrives in the SMAMX environment, it can be proven by the many achievements of Tapak Suci that have been achieved by students. This study seeks to find out the habitus and capital possessed by students in achieving achievements in the field of sacred sites. This study uses a qualitative method, a case study approach. The research location is in SMAMX with 7 informants who are active students participating in the sacred tapak training and winning various sacred tapak competitions. Data collection techniques through observation, interviews, and documentation. The data analysis technique uses the Miles and Hubermen model technique, namely data reduction, data presentation, verification, and conclusion drawing. This study uses Pierre Bourdieu’s theory of habitus. The findings of the data show that the educational atmosphere is supported by existing regulations making students accustomed to competition in non-academics between students and considers non-academics to be more than academics. SMAMX is seen as a talent school compared to a normal school. From the findings of data that has been managed by classifying and combined with Bourdieu’s theory of capital, it can be concluded that students have 4 types of capital in achieving achievements, including cultural, economic, social, and symbolic capital. where each informant has a different capacity and size of capital. it becomes a benchmark for the difference in achievement of each informant. Keyword :Tapak Suci,SMAMX, Habit, Field, Capital.